Hydrogel patch for wound sealing and repairing as well as preparation method and application of hydrogel patch
By using hydrogel patches made of UV cross-linked materials such as gelatin, the problem of local dehydration of wounds caused by dry double-sided tape is solved, and a moist environment is built at the wound, promoting healing, and accelerating and improving the wound healing process.
Patent Information
- Application Number
- CN202411858405.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
After the existing dry double-sided tape is used at the wound, it may cause local dehydration of the wound, forming scabs, hindering the growth and repair of epithelial cells, and thus affecting the skin healing effect.
A hydrogel patch made of gelatin, N-acrylylated amino acids, N-succinimide acrylate, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone and water through ultraviolet light crosslinking is used to provide an adhesive layer and an anti-adhesive layer to form an aqueous gel material, the mechanical strength meets the needs of repair, and a moist healing environment is constructed at the wound.
This hydrogel patch can build a moist healing environment on external wounds, promote the release of various growth factors, facilitate the healing of skin wounds, speed up healing time, and improve healing effect.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogel patches, and in particular relates to a hydrogel patch for wound sealing and repairing, and a preparation method and application thereof. Background Art
[0002] A novel dry double-sided adhesive tape is prepared from biopolymers such as gelatin or chitosan and polyacrylic acid grafted with N-succinimidyl ester, which is a biodegradable material.
[0003] In order to pursue strong mechanical properties, dry double-sided tape needs to be dried and adhered to the wound, which will absorb interfacial water and may cause local dehydration of the wound surface, form scabs, and hinder the growth and repair of epithelial cells. Therefore, the effect of promoting skin healing is poor. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a hydrogel patch for wound sealing and repair, and a preparation method and application thereof. The hydrogel patch has a mechanical strength that meets the repair requirements, can form a moist healing environment for wounds in vitro, promote the release of multiple growth factors, and is beneficial to skin wound healing.
[0005] The present invention provides a wound sealing and repairing hydrogel patch, comprising an adhesive layer;
[0006] The adhesive layer is prepared by cross-linking gelatin, N-acrylylated amino acid, acrylic acid-N-succinimide ester, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone and water through ultraviolet light.
[0007] Preferably, the N-acryloylated amino acid is selected from one or more of N-acryloylated glycine, N-acryloylated aspartic acid and N-acryloylated glutamic acid.
[0008] Preferably, the mass ratio of the gelatin, N-acryloyl amino acid, acrylic acid-N-succinimidyl ester, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and water is 10:(20-30):1:(0.2-0.3):30:100.
[0009] Preferably, the invention further comprises an anti-adhesion layer, which is prepared by cross-linking methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and water through ultraviolet light.
[0010] Preferably, the mass ratio of the methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and water is 10:7:0.2:100.
[0011] In the wound sealing and repairing hydrogel patch, the molecular weight of the polyethylene glycol diacrylate is 350-450.
[0012] The present invention provides a method for preparing the wound sealing and repairing hydrogel patch according to the above technical solution, comprising the following steps:
[0013] gelatin, N-acryloyl amino acid, acrylic acid-N-succinimidyl ester and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone are added into sterile water for dissolution to obtain an adhesive layer aqueous solution, which is cross-linked by ultraviolet light to obtain an adhesive layer;
[0014] Methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone are added into sterile water and dissolved to obtain an anti-adhesion layer aqueous solution;
[0015] The anti-adhesion layer aqueous solution is injected into the upper layer of the adhesion layer, and then subjected to ultraviolet cross-linking to obtain a wound sealing and repairing hydrogel patch.
[0016] Preferably, the wavelength used for the ultraviolet cross-linking is 365 nm, and the time of ultraviolet cross-linking is 20 to 60 minutes.
[0017] The present invention also provides an application of the wound sealing and repairing hydrogel patch described in the above technical solution in the preparation of a skin wound repair patch, a liver incision repair patch or a gastric incision repair patch.
[0018] The present invention provides a wound sealing and repairing hydrogel patch, comprising an adhesive layer; the adhesive layer is made of gelatin, N-acrylylated amino acid, acrylic acid-N-succinimidyl ester, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and water through ultraviolet cross-linking. The hydrogel patch provided by the present invention can be used for sealing and repairing wounds of various tissues, accelerating the healing time and improving the healing effect, such as skin tissue, liver tissue and stomach tissue. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 1 is the H NMR spectrum of N-acryloylated glycine, N-acryloylated aspartic acid and N-acryloylated glutamic acid (from top to bottom);
[0020] Figure 2 Young's modulus diagram of the hydrogel patches prepared in Example 2, Example 3 and Example 4;
[0021] Figure 3 The breaking strength diagram of the hydrogel patches prepared in Example 2, Example 3 and Example 4;
[0022] Figure 4The elongation at break graphs of the hydrogel patches prepared in Example 2, Example 3 and Example 4;
[0023] Figure 5 The adhesion strength measured by lap shear of the hydrogel patches prepared in Example 2, Example 3 and Example 4;
[0024] Figure 6 is a curve showing the change in mass of the single-layer hydrogel patch and the anti-adhesion layer hydrogel after freeze-drying over time in Example 12;
[0025] Figure 7 The photos and HE sections of the dorsal tissues implanted with single-layer hydrogel patches and anti-adhesion layer hydrogels at different time points;
[0026] Figure 8 The photos of the back incision healing of rats in each group at different time points;
[0027] Fig. 9 HE sections were obtained from the incision sites of rats in each group on the 7th and 14th days;
[0028] Fig.10 is the statistical result of wound area;
[0029] Fig.11 These are the stomach photos of rats in the gastric suture group and the double-layer patch group that were untreated, on day 0, and on day 20. DETAILED DESCRIPTION
[0030] The present invention provides a wound sealing and repairing hydrogel patch, comprising an adhesive layer;
[0031] The adhesive layer is prepared by cross-linking gelatin, N-acrylylated amino acid, acrylic acid-N-succinimide ester, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone and water through ultraviolet light.
[0032] The hydrogel patch provided by the present invention is a water-containing gel material, the mechanical strength of which meets the repair requirements, can form a moist healing environment for wounds in vitro, promote the release of multiple growth factors, and is beneficial to the healing of skin wounds.
[0033] The mass ratio of gelatin, N-acryloyl amino acid, acrylic acid-N-succinimide ester, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959) and water in the present invention is 10:(20-30):1:(0.2-0.3):30:100.
[0034] The water used in the present invention is sterile water.
[0035] In the present invention, the N-acryloylated amino acid is selected from one or more of N-acryloylated glycine, N-acryloylated aspartic acid and N-acryloylated glutamic acid.
[0036] The N-acryloyl amino acid described in the present invention is prepared according to the following method:
[0037] The amino acid is dissolved and reacted with acryloyl chloride to obtain N-acryloylated amino acid.
[0038] The molar ratio of the amino acid to acryloyl chloride in the present invention is 1:1 to 1:1.5, and the reaction time is 2.5 to 6 hours. The amino acid is glycine, aspartic acid or glutamic acid.
[0039] In the present invention, the reaction formula of the N-acryloylated glycine is:
[0040]
[0041] The reaction formula for N-acrylylation of aspartic acid is:
[0042]
[0043] The reaction formula with N-acryloylated glutamic acid is:
[0044]
[0045] The present invention preferably uses a sodium hydroxide aqueous solution to dissolve aspartic acid. The present invention has no special restrictions on the dissolution process, and a dissolution technical solution well known to those skilled in the art can be used. The molar equivalent of the sodium hydroxide is preferably 3 times that of aspartic acid; the molar equivalent of water is preferably 60 times that of aspartic acid; the dissolution temperature is preferably 0°C; and the dissolution time is preferably 15 minutes.
[0046] Acryloyl chloride is preferably added to tetrahydrofuran solvent to obtain an acryloyl chloride solution; in the present invention, the acryloyl chloride solution is preferably added dropwise to an aspartic acid aqueous solution for reaction; the molar equivalent of the acryloyl chloride is 1 times that of aspartic acid, and the molar equivalent of the tetrahydrofuran is preferably 3 times that of aspartic acid. In the present invention, the temperature for adding the acryloyl chloride solution dropwise is preferably 0°C, and the time for adding the acryloyl chloride solution dropwise is preferably 10 minutes.
[0047] In the present invention, the reaction is preferably carried out under stirring conditions; the reaction temperature is 25°C, and the reaction time is 3.5 hours. After the reaction is completed, the present invention preferably adds sodium hydroxide aqueous solution to adjust the pH value, preferably to 11-12; the concentration of the sodium hydroxide aqueous solution is 2 mol / L. Washing is performed after the pH value is adjusted; the present invention preferably uses ethyl acetate and the reaction solution to mix to produce stratification, and the product is in the aqueous phase.
[0048] After washing, the present invention preferably adds hydrochloric acid solution dropwise to adjust the pH value again, the concentration of the hydrochloric acid solution is 6 mol / L, and the pH value is adjusted to 1 to 2 again. After adjusting the pH value again, extraction is performed to obtain an aqueous phase; the present invention preferably uses ethyl acetate extraction; the extraction of the aqueous phase can be performed using a technical solution well known to those skilled in the art.
[0049] After the extraction, the present invention uses anhydrous magnesium sulfate to dry, filters to obtain a liquid phase, concentrates it, precipitates it with ice n-hexane, filters it, obtains a solid, and vacuum evacuates it to obtain N-acryloylated aspartic acid. The present invention preferably uses a rotary evaporator for concentration; the concentration temperature is 30° C. The drying, filtering, and precipitation in the present invention can be carried out by using technical solutions well known to those skilled in the art.
[0050] In the present invention, the preparation method of N-acryloylated glutamic acid is the same as that of N-acryloylated aspartic acid.
[0051] In the present invention, the preparation method of N-acryloylated glycine is the same as that of N-acryloylated aspartic acid except that the molar equivalent of sodium hydroxide is preferably 2.3 times that of glycine. The remaining preparation steps are the same as those of N-acryloylated aspartic acid.
[0052] The wound sealing and repairing hydrogel patch provided by the present invention can be added with an anti-adhesion layer according to the usage scenario to avoid tissue adhesion; the anti-adhesion layer is prepared by cross-linking methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and water through ultraviolet light.
[0053] The present invention adopts two anti-adhesion components, methacryloylethyl sulfobetaine and polyethylene glycol diacrylate, to construct an anti-adhesion layer, so that the hydrogel patch can treat wounds in the body, thereby greatly broadening the application range of the material.
[0054] In the present invention, the mass ratio of methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959) and water is 10:7:0.2:100.
[0055] In the present invention, the molecular weight of the polyethylene glycol diacrylate is 350-450; in a specific embodiment, the molecular weight of the polyethylene glycol diacrylate is 400.
[0056] The present invention provides a method for preparing the wound sealing and repairing hydrogel patch according to the above technical solution, comprising the following steps:
[0057] gelatin, N-acryloyl amino acid, acrylic acid-N-succinimidyl ester and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone are added into sterile water for dissolution to obtain an adhesive layer aqueous solution, which is cross-linked by ultraviolet light to obtain an adhesive layer;
[0058] Methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone are added into sterile water and dissolved to obtain an anti-adhesion layer aqueous solution;
[0059] The anti-adhesion layer aqueous solution is injected into the upper layer of the adhesion layer, and then subjected to ultraviolet cross-linking to obtain a wound sealing and repairing hydrogel patch.
[0060] The present invention adds gelatin, N-acryloyl amino acid, acrylic acid-N-succinimide ester and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone into sterile water for dissolution to obtain an adhesive layer aqueous solution, and then crosslinks the adhesive layer by ultraviolet light. In the present invention, the mass concentration of gelatin in the adhesive layer aqueous solution is preferably 10%, the mass concentration of N-acryloyl amino acid is preferably 20-30% (w / v), the mass concentration of acrylic acid-N-succinimide ester is preferably 1%, and the mass concentration of I2959 is preferably 0.2-0.3%; the N-acryloyl amino acid is preferably N-acryloyl aspartic acid, and its mass concentration is 30%.
[0061] After the adhesive layer aqueous solution is prepared, the present invention injects it into a mold made of a release film and a silicone gasket, and crosslinks it under ultraviolet light to form a hydrogel patch adhesive layer. The time for preparing the adhesive layer by light crosslinking is 20 to 60 minutes.
[0062] In the present invention, methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone are added to sterile water to dissolve to obtain an anti-adhesion layer aqueous solution. In a specific embodiment of the present invention, the mass concentration of methacryloylethyl sulfobetaine in the anti-adhesion layer aqueous solution is preferably 10%, the molecular weight of polyethylene glycol diacrylate is preferably 400, the mass concentration is preferably 7%, and the mass concentration of I2959 is preferably 0.2%.
[0063] The present invention preferably places the adhesive layer in a mold, then injects the aqueous solution of the anti-adhesion layer into the upper layer of the adhesive layer, and crosslinks the anti-adhesion layer of the hydrogel patch under ultraviolet light. The wavelength used for the ultraviolet crosslinking is 365nm, and the time of ultraviolet crosslinking is 30 to 60 minutes; in a specific embodiment, the time of ultraviolet crosslinking is 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes.
[0064] The hydrogel patch provided by the present invention is essentially a hydrogel, containing water, which can keep the skin wound moist, help cell proliferation and recovery, and thus accelerate the healing of the skin wound. From the perspective of biocompatibility, the prepared material has good blood compatibility, cell compatibility and animal tissue compatibility, which are within the safety range.
[0065] The present invention also provides an application of the wound sealing and repairing hydrogel patch described in the above technical solution in the preparation of a skin wound repair patch, a liver incision repair patch or a gastric incision repair patch.
[0066] To further illustrate the present invention, a hydrogel patch for wound sealing and repairing provided by the present invention, a preparation method thereof and applications thereof are described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0067] Example 1
[0068] Under ice-water bath conditions, 20 g of aspartic acid and 18 g of sodium hydroxide were dissolved in 160 mL of water, and 13.6 mL of acryloyl chloride was added to 30 mL of tetrahydrofuran, and then the tetrahydrofuran solution of acryloyl chloride was added dropwise to the aqueous solution, and the temperature was changed to 25°C, and then the reaction was continued for 3.5 hours. The pH was adjusted to 11 with sodium hydroxide solution, washed with ethyl acetate to obtain an aqueous phase, and then the pH was adjusted to 1 with concentrated hydrochloric acid, and extracted with ethyl acetate. After drying, filtering, concentrating, settling and vacuum drying were performed to obtain N-acryloylated aspartic acid.
[0069] Then, N-acryloylated glycine and N-acryloylated glutamic acid were prepared by corresponding methods.
[0070] Among them, the difference in the preparation of N-acryloylated glycine is that, under ice-water bath conditions, 20g of glycine and 24.9g of sodium hydroxide are dissolved in 220mL of water, 25mL of acryloyl chloride is added to 54mL of tetrahydrofuran, and then the tetrahydrofuran solution of acryloyl chloride is added dropwise to the aqueous solution, and the temperature is changed to 25°C, and then the reaction is continued for 3.5 hours. The pH is adjusted to 11 with sodium hydroxide solution, the aqueous phase is washed with ethyl acetate, and the pH is adjusted to 1 with concentrated hydrochloric acid, and extracted with ethyl acetate. After drying, filtering, concentration, sedimentation and vacuum drying are performed, N-acryloylated glycine is obtained.
[0071] Figure 1 From top to bottom are the nuclear magnetic resonance hydrogen spectra of N-acryloylated glycine, N-acryloylated aspartic acid and N-acryloylated glutamic acid.
[0072] Embodiment 2:
[0073] Add 1 g of gelatin, 3 g of N-acryloylated glycine, 100 mg of acrylic acid-N-succinimidyl ester and 30 mg of I2959 into 10 mL of sterile water to dissolve, then transfer it to a mold and irradiate it under a 365 nm ultraviolet light source for 40 minutes to obtain a hydrogel patch adhesive layer.
[0074] Embodiment 3:
[0075] Add 1 g of gelatin, 3 g of N-acryloylated aspartic acid, 100 mg of acrylic acid-N-succinimidyl ester and 30 mg of I2959 into 10 mL of sterile water to dissolve, then transfer it to a mold and irradiate it under a 365 nm ultraviolet light source for 40 minutes to obtain a hydrogel patch adhesive layer.
[0076] Embodiment 4:
[0077] 1 g of gelatin, 3 g of N-acryloylated glutamic acid, 100 mg of acrylic acid-N-succinimidyl ester and 30 mg of I2959 were added to 10 mL of sterile water to dissolve, and then transferred to a mold and irradiated under a 365 nm ultraviolet light source for 40 minutes to obtain a hydrogel patch adhesive layer.
[0078] Embodiment 5:
[0079] Add 1g of methacryloylethyl sulfobetaine, 700mg of polyethylene glycol diacrylate (molecular weight 400), and 20mg of I2959 to 10mL of sterile water and dissolve them. Then transfer them to a mold where an adhesive layer has been placed in advance. Irradiate the mold under a 365nm ultraviolet light source for 30 minutes to obtain a double-layer hydrogel patch.
[0080] Embodiment 6:
[0081] The three hydrogel patches prepared in Example 2, Example 3 and Example 4, namely, the hydrogel patch containing N-acryloylated glycine, the hydrogel patch containing N-acryloylated aspartic acid and the hydrogel patch containing N-acryloylated glutamic acid, were cut into sizes of 3*1.5*0.1 cm, and then their tensile properties were measured using a universal testing machine. Figure 2 , Figure 3 and Figure 4 The abbreviations of the hydrogel patch containing N-acryloylated glycine, the hydrogel patch containing N-acryloylated aspartic acid and the hydrogel patch containing N-acryloylated glutamic acid are AGLY, AASP and AGLU respectively.
[0082] from Figure 2 It can be seen that the Young’s moduli of AGLY, AASP, and AGLU are 105.60 ± 30.52 kPa, 7.11 ± 0.23 kPa, and 17.53 ± 7.55 kPa, respectively;
[0083] from Figure 3 It can be seen that the breaking strengths of AGLY, AASP, and AGLU are 211.80±27.91kPa, 17.43±4.10kPa, and 27.79±8.49kPa, respectively;
[0084] from Figure 4 It can be seen that the elongation at break of AGLY, AASP and AGLU are 550.33±166.68%, 1084.50±370.51% and 379.87±123.97%, respectively.
[0085] Embodiment 7:
[0086] The three hydrogel patches prepared in Example 2, Example 3 and Example 4, namely, the hydrogel patch containing N-acryloylated glycine, the hydrogel patch containing N-acryloylated aspartic acid and the hydrogel patch containing N-acryloylated glutamic acid, were cut into sizes of 1.5*1.5*0.1 cm, and the pig skin with fat scraped off was cut into sizes of 1.5*4.5 cm. Then, the hydrogel patch was pasted between two pig skins, and a 200 g weight was pressed on the pig skin pasting site for 1 hour, and then the lap shear properties of the three hydrogel patches were measured using a universal testing machine. Figure 5 The adhesion strength of the three hydrogel patches measured by lap shear. The abbreviations of the hydrogel patch containing N-acryloylated glycine, the hydrogel patch containing N-acryloylated aspartic acid, and the hydrogel patch containing N-acryloylated glutamic acid are AGLY, AASP, and AGLU, respectively.
[0087] from Figure 5 It can be seen that the lap shear adhesion strengths of AGLY, AASP and AGLU are 44.13±8.17 kPa, 58.83±5.57 kPa and 13.79±2.25 kPa, respectively.
[0088] Embodiment 8:
[0089] The hydrogel patch prepared in Example 5 (adhesive layer is Example 3) was cut into 3*1.5*0.1 cm sizes, and then its tensile properties were measured using a universal testing machine. The Young's modulus was 92.9±28.5 kPa, the breaking strength was 0.29±0.03 N, and the breaking elongation was 77%±31%.
[0090] Embodiment 9:
[0091] The double-layer hydrogel patch prepared in Example 5 was divided into 1.5×1.5×0.1 cm in size, and the pig skin with fat scraped off was divided into 1.5×4.5 cm in size. Then, the hydrogel patch was pasted between two pieces of pig skin, and a 200 g weight was pressed on the pig skin adhesion area for 1 hour. Then, the lap shear performance of the double-layer hydrogel patch was measured with a universal testing machine, and the adhesion strength was measured to be 0.80±0.40 kPa.
[0092] Embodiment 10:
[0093] Take 3g of the double-layer hydrogel patch prepared in Example 5 (the adhesive layer is Example 3) and add 15mL of PBS solution with pH = 7.4, and extract at 37°C for 12 hours. After 12 hours, the extract was aspirated and diluted with PBS solution to prepare solutions with 50vol% and 25vol% extract concentrations. Add 300μL of 100 vol%, 50vol%, and 25vol% extracts to 1.5mL centrifuge tubes respectively, and add red blood cell lysate and PBS solution to two groups as positive and negative groups, and then add 300μL of 2% rabbit red blood cells to each centrifuge tube and incubate at 37°C for two hours. After centrifugation, draw 200μL of supernatant into a 96-well plate and detect the absorbance at 540nm with an enzyme marker. See Table 1 for the results, which shows the hemolysis rate data of extracts of different concentrations.
[0094] Table 1
[0095]
[0096] Embodiment 11:
[0097] Take 3g of the double-layer hydrogel patch prepared in Example 5 (the adhesive layer is Example 3) and add 15m of DMEM culture medium solution containing 10% fetal bovine serum, and extract at 37°C for 12 hours. After 12 hours, the extract was aspirated and diluted with a DMEM culture medium solution containing 10% fetal bovine serum to prepare a solution with an extract concentration of 50vol%, 25vol%, 12.5vol%, and 6.75vol%. L929 cells were inoculated in a 96-well plate, with 9000 cells inoculated per well. After incubation at 37°C for 24 hours, the previous culture medium was replaced with 200μL of extracts of different concentrations, and the control group replaced the previous culture medium with fresh culture medium. After incubation for 24 hours, the previous culture medium was replaced with 200μL of fresh culture medium containing 10% (v / v) CCK-8 solution. After incubation at 37°C for 2 hours, the absorbance at 450nm was measured with an enzyme marker. The results are shown in Table 2, which shows the cell survival rate of extracts of different concentrations.
[0098] Table 2
[0099]
[0100] Example 12
[0101] 1 g of methacryloylethyl sulfobetaine, 700 mg of polyethylene glycol diacrylate (molecular weight 400), and 20 mg of I2959 were added to 10 mL of sterile water to dissolve, and then transferred to a mold and irradiated under a 365 nm ultraviolet light source for 30 minutes to obtain a separate anti-adhesion layer hydrogel. After anesthetizing male SD rats aged 6-8 weeks with isoflurane, the hydrogel patch prepared in Example 3 and a separate anti-adhesion layer hydrogel were implanted in their backs, and the back tissue was taken regularly and the mass of the hydrogel after freeze-drying was weighed. Results are shown in Figure 6 and Figure 7 , Figure 6 The curves of the mass change of the single-layer hydrogel patch and the anti-adhesion layer hydrogel after freeze-drying over time are shown in Figure 2. Figure 7 These are photos and HE sections of the dorsal tissue implanted with a single-layer hydrogel patch and an anti-adhesion layer hydrogel at different time points.
[0102] OLP is the material prepared in Example 3. Anti-adhesion layer is a separate anti-adhesion layer hydrogel. Figure 6 It showed that OLP rapidly degraded before the 20th day and was basically degraded by the 40th day. The anti-adhesion layer hydrogel had not been completely degraded at the eighth week and was still in the degradation process.
[0103] Figure 7 The degradation of tissue was qualitatively observed from photos and HE sections. Figure 6 The data are consistent with those of the previous study, and HE sections show that the inflammation of the surrounding tissues is normal and the material has good biocompatibility.
[0104] Embodiment 13
[0105] The invention is used for hemostasis of rat liver.
[0106] Male SD rats were selected, weighing about 220 g. 30 minutes before the operation, 3000 U / kg heparin calcium solution was intraperitoneally injected for anticoagulation treatment, and then the rats were anesthetized with isoflurane. The left liver of the rat was fully exposed through an abdominal incision, and a 1 cm incision was made on the liver with a scalpel. When the liver was actively bleeding, the hydrogel patch prepared in Example 5 (the adhesive layer was Example 3) and fibrin glue were used to cover the wound, and the amount of bleeding was recorded. The results are shown in Table 3, which is a comparison of the amount of bleeding in rats of different groups.
[0107] Table 3
[0108]
[0109] Embodiment 14
[0110] The invention is used for healing full-thickness skin incisions of rats.
[0111] Male SD rats, 6-8 weeks old, were selected for the rats. After being anesthetized with isoflurane, the hair on their backs was shaved and disinfected with iodine. A full-thickness skin incision of about 2 cm in length was made on the backs of the rats with a scalpel, and then the hydrogel patch prepared in Example 3 was applied. The control groups included a blank group, a surgical suture group, a fibrin glue group, and a cyanoacrylate group. Pictures were taken regularly, and tissues were sliced to evaluate the wound healing effect. The results are shown in Figure 8 , Fig. 9 and Fig.10 , Figure 8 These are photos of the back incision healing of rats in each group at different time points. Fig. 9 HE sections of the incision tissues of rats in each group on the 7th and 14th days. Fig.10 is the statistical result of wound area. The blank group is Untreated, the suture group is Suture, the fibrin glue group is Fibringlue, the cyanoacrylate group is Cyanoacrylate, and the hydrogel patch prepared in Example 3 is OLP;
[0112] Figure 8 It showed that OLP had the best healing effect, with a small incision surface area, and the incision was basically healed on the 10th day, while the other groups still showed incomplete healing. Fig. 9 HE sections of the incision tissue also show that the incision healing effect of OLP is good. Fig.10 Yes Fig. 9 The results were quantitatively analyzed and the wound area was expressed as shown in Table 4 below:
[0113] Table 4
[0114]
[0115] Embodiment 15
[0116] The invention is used for healing gastric incision of rats.
[0117] Male SD rats, 6-8 weeks old, were selected as mice. They were deprived of water and food for one day before the experiment. After the mice were anesthetized with isoflurane, their abdominal hair was shaved and disinfected with iodine. The abdominal skin was cut with a scalpel to fully expose the stomach of the mice. A 7 mm incision was made in the stomach with a scalpel, and the hydrogel patch prepared in Example 5 (the adhesive layer was Example 3) was attached. The control group was sutured with sutures. Then the abdominal cavity was closed, the skin was sutured, and observation was made after 20 days. The results are shown in Fig.11 , Fig.11 These are the stomach photos of rats in the gastric suture group and the double-layer patch group that were untreated, on day 0, and on day 20. Fig.11It can be seen that the incisions of the gastric suture group and the double-layer patch group were basically healed, but the suture group had additional damage to the tissues caused by the sutures, while the double-layer patch group could achieve damage-free healing.
[0118] It can be seen from the above embodiments that the present invention provides a wound sealing and repairing hydrogel patch, including a single adhesive layer and two types of adhesive layers and anti-adhesion layers; the adhesive layer is made of gelatin, N-acryloyl amino acids, acrylic acid-N-succinimidyl ester, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and water by ultraviolet crosslinking; the anti-adhesion layer is made of methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and water by ultraviolet crosslinking. The hydrogel patch provided by the present invention can be used for the sealing and repair of wounds of various tissues (skin tissue, liver tissue and gastric tissue), accelerate the healing time, and improve the healing effect. The experimental results show that the hydrogel patch can shorten the healing time of skin incisions from 14 days to 10 days. From the macroscopic photos and related sections, it can be seen that the group of the present invention is superior to other treatment methods, and can achieve non-damaging healing for gastric wounds.
[0119] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A wound sealing and repairing hydrogel patch, characterized in that: including an adhesive layer; The adhesive layer is prepared by cross-linking gelatin, N-acrylylated amino acid, acrylic acid-N-succinimide ester, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone and water through ultraviolet light.
2. The wound sealing and repairing hydrogel patch according to claim 1, characterized in that: The N-acryloylated amino acid is selected from one or more of N-acryloylated glycine, N-acryloylated aspartic acid and N-acryloylated glutamic acid.
3. The wound sealing and repairing hydrogel patch according to claim 1, characterized in that: The mass ratio of the gelatin, N-acryloyl amino acid, acrylic acid-N-succinimide ester, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and water is 10:(20-30):1:(0.2-0.3):30:
100.
4. The wound sealing and repairing hydrogel patch according to claim 1, characterized in that: The invention also comprises an anti-adhesion layer, which is prepared by cross-linking methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and water through ultraviolet light.
5. The wound sealing and repairing hydrogel patch according to claim 4, characterized in that: The mass ratio of the methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and water is 10:7:0.2:
100.
6. The wound sealing and repairing hydrogel patch according to claim 4, characterized in that: The molecular weight of the polyethylene glycol diacrylate is 350-450.
7. A method for preparing the wound sealing and repairing hydrogel patch according to any one of claims 1 to 6, comprising the following steps: gelatin, N-acryloyl amino acid, acrylic acid-N-succinimidyl ester and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone are added into sterile water for dissolution to obtain an adhesive layer aqueous solution, which is cross-linked by ultraviolet light to obtain an adhesive layer; Methacryloylethyl sulfobetaine, polyethylene glycol diacrylate, and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone are added into sterile water and dissolved to obtain an anti-adhesion layer aqueous solution; The anti-adhesion layer aqueous solution is injected into the upper layer of the adhesion layer, and then subjected to ultraviolet cross-linking to obtain a wound sealing and repairing hydrogel patch.
8. The preparation method according to claim 7, characterized in that: The wavelength used for the ultraviolet cross-linking is 365 nm, and the time for the ultraviolet cross-linking is 20 to 60 minutes.
9. Use of the wound sealing and repairing hydrogel patch according to claim 1 in preparing a skin wound repair patch, a liver incision repair patch or a gastric incision repair patch.
Citation Information
Cited By
Gelatin / polyacrylic acid / NHS-AAc composite in-situ hemostatic hydrogel patch and preparation method thereof
CN122461543A